PROFITABILITY AND MARKET VALUE ON STOCK PRICE: FIRM SIZE MODERATION IN PUBLIC COMPANIES IN INDONESIA - Endra Wahyu Ningdiyah; Ruci Arizanda Rahayu; Wiwit Hariyanto (E-Jurnal Akuntansi TSM, 2026)
This study aims to analyze the influence of profitability, market value, and firm size on the stock prices of pharmaceutical companies and examine the role of moderating variables in strengthening this relationship. The pharmaceutical industry was chosen as the research object due to its innovation-intensive nature, tight regulation, and stock price dynamics that do not always align with the company's fundamental performance. This study employed a quantitative approach using the Partial Least Squares–Structural Equation Modeling (PLS-SEM) method. The research data consisted of secondary data obtained from financial reports and stock price data of pharmaceutical companies listed on the Indonesia Stock Exchange during a specific observation period. The analysis technique involved evaluating the measurement model (outer model) and the structural model (inner model), as well as testing hypotheses using bootstrapping procedures. The results showed that profitability, market value, and firm size had a positive and significant effect on stock prices. Furthermore, the results of the moderating variable test indicated that the moderating variables were able to strengthen the relationship between the company's fundamental variables and stock prices. The research model has strong explanatory power, as demonstrated by a high coefficient of determination and the fulfillment of all validity and reliability criteria. This research provides a theoretical contribution by enriching the capital market literature on stock price formation mechanisms, particularly in the pharmaceutical sector, with an emphasis on the important role of moderating variables. Practically, the results of this study can be used as a consideration by company management and investors when making investment decisions based on fundamental company information